The effect of organizational culture on the organization's performance :Field research at the Central Bank of Iraq - Faeq Al-Shihabi, Areej; Jawad Abdul, Nazem (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to achieve a set of basic objectives that include diagnosing the level of the organizational culture of the Central Bank of Iraq. And measure the effect of organizational culture on the performance of the Central Bank of Iraq. And activating the role of organizational culture in the Central Bank of Iraq based on scientific and practical justifications and working to enhance the organization's performance in it. The central bank represented the researched population, while the research sample was represented by a group of central bank employees with 240 individuals representing respondents to the research questionnaire, which consisted of 25 items to measure the organizational culture and 14 items to measure the organization's performance, and a set of statistical means was used to analyze the data, including frequency distribution, percentages, arithmetic mean, standard deviation, variation coefficient, alpha-Cronbach stability factor, Pearson correlation coefficient, and simple linear regression model, through statistical programs SPSS V. 24 and Amos v. 24. However, the research reached a set of conclusions. One of the most important is that the organizational culture in the Central Bank of Iraq directly affects performance. As for the level of dimensions, symbols, organizational values, organizational expectations, and organizational beliefs, rituals have had a good effect on performance.